PENGELOLAAN PUNGUTAN RETRIBUSI KENDARAAN ANGKUTAN UMUM DI TERMINAL TANJUNGPURI OLEH DINAS PERHUBUNGAN KABUPATEN SINTANG - Erwandi, Antonius (Universitas Kapuas Sintang, 2024)
Public transport levies are one aspect that contributes to Regional Original Income that needs to be improved so that the management of these levies must be effective and transparent. This research aims to uncover the problem of managing public transport vehicle levies at the Tanjungpuri Terminal by the Sintang Regency Transportation Service. Qualitative research method with a descriptive analysis approach. The research results show that the levy mechanism is carried out by officers directly by visiting public transport vehicles entering the terminal with each entry counting as one stop. However, there are still public transport vehicles dropping off passengers outside the terminal without supervision. Officers monitor levies by visiting each terminal to ensure officers are always there during working hours and checking bookkeeping reports.